Fatty acid profiles and health fatty acid indices of traditional cheeses of southeastern European countries - Miroljub Barać; Zlatan Sarić (Mljekarstvo)
Different types of traditional cheeses have a central place in the markets of southeast European countries. They are usually produced as artisanal from cow’s, sheep’s and rarely goat’s milk. In the last twenty years, these cheeses have attracted numerous researchers’ attention. Most of these investigations have been focused on the specificity of their production and the proteolytic changes that influence the nutritional and sensory properties of specific cheese varieties. Less attention has been paid to their fatty acid profiles and their possible effects on human health. Since fatty acids content in cheeses are affected by numerous factors (type of milk and its characteristics, breeding, feeding, geographical area, and the production process), it can be assumed that their fatty acid composition (profiles) is significantly different. This paper provides an overview of the current knowledge of fatty acid profiles and health-related fat indices of traditional cheeses from several southeast European countries including Serbia, Bosnia and Herzegovina, Montenegro and North Macedonia.